A novel pattern agile microstrip antenna for modern wireless communication systems. Issue 2 (17th February 2023) - Sharma, Abha; Yadav, Ajay; Rathi, Amit
ABSTRACT: This article presents a circular microstrip patch antenna loaded with three complementary split rings (CSRRs) on the ground plane for pattern agility features. The antenna resonated at 5.3 GHz and accommodated the frequency spectrum from 5.1–5.7 GHz for different CSRR combinations. The reconfigurable pattern feature has been produced with three p-i-n diode combinations integrated with the CSRR slot on the ground patch. The CSRR combinations are utilized to change the radiation phase concerning the primary radiating circular patch. The proposed antenna radiation beam can steer from ±15°, 180°, and 0° of the broadside pattern in the elevation plane with a satisfactory gain of 3 dBi. The phase variation for various CSRR combinations concerning the primary antenna is presented. The presented antenna is fabricated on an FR4 substrate and tested in an anechoic environment; the tested results verify the pattern agility of the antenna. The demonstrated antenna is suitable for modern wireless communications like LTE and Cognitive radios. The compact size, simple biasing, and low cost are added advantages of the antenna.